Impact of initial therapy with upadacitinib or adalimumab on achievement of 48-week treatment goals in patients with rheumatoid arthritis: post hoc analysis of SELECT-COMPARE - Mysler, E; Tanaka, Y; Kavanaugh, A; Aletaha, D; Taylor, PC; Song, I-H; Shaw, T; Song, Y; DeMasi, R; Ali, M; Fleischmann, R (Oxford University Press, 2022)
Objectives Evaluate the importance of treatment sequencing in SELECT-COMPARE, assessing potential differences between starting upadacitinib or adalimumab therapy following inadequate MTX response. Methods Patients from SELECT-COMPARE were randomized to upadacitinib 15 mg once daily, placebo or adalimumab 40 mg. Per protocol, patients with <20% improvement in tender or swollen joint counts (weeks 14, 18, 22) or failure to achieve Clinical Disease Activity Index (CDAI) low disease activity (LDA) at week 26 were blindly switched from upadacitinib to adalimumab or vice versa. Treatment outcomes, including clinical remission/LDA, physical function, pain and a novel combined endpoint for deep response, were evaluated through 48 weeks and corresponding time-averaged response rates determined. Data were analysed by initial randomized group regardless of any subsequent switch in therapy. Results This post hoc analysis included 651 patients initially randomized to upadacitinib (of whom 252 switched to adalimumab) and 327 patients initially randomized to adalimumab (of whom 159 switched to upadacitinib). At week 48, patients randomized to either therapy demonstrated similar achievement of most treatment endpoints. Greater improvements in the total time spent in a lower disease state were observed for initial upadacitinib vs initial adalimumab therapy across most clinical and patient-reported outcomes through 48 weeks, and the median time to DAS28(CRP) <2.6/≤3.2 occurred 6–8 weeks earlier among those randomized to upadacitinib. Conclusion Following a modified treat-to-target strategy, rates of CDAI remission/LDA and DAS28(CRP) <2.6/≤3.2 at 48 weeks were similar, regardless of starting therapy. However, patients initially receiving upadacitinib reached treatment targets more quickly and spent more time in clinical targets over the initial 48 weeks of treatment. Trial registration ClinicalTrials.gov, https://clinicaltrials.gov, NCT02629159